GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PADA SD NEGERI LAMBARO ANGAN - Siti Nurbaya M. Ali; Cut Zahri Harun; Djailani AR (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: Style or manner of a school principal in his capacity as leader largely determine success in improving teacher performance under his leadership. The purpose of this study was to obtain data on (1) the principal's leadership style in improving labor discipline, (2) the principal's leadership style to motivate the work of teachers, (3) the principal's leadership style in increasing responsibilities and (4) constraints faced by principals in improving teacher performance. By using a qualitative approach, data collection techniques of observation, interviews and documentary studies, research subjects principals, and teachers, the data analysis techniques with qualitative analysis. This study shows that (1) the principal's leadership style instructive apply (telling) in improving discipline, (2) applying the principal consultative leadership style (selling) in improving work motivation of teachers, (3) the principal's leadership style apply discretionary (delegating) in improving the teacher's responsibility, and (4) the obstacles faced by the school principal that the decline in teacher discipline, teacher performance lack of motivation, and low sense of responsibility in the learning of teachers. It is recommended that the principals can implement a better leadership style or varied so that the desired goal can be achieved with good and maximum.Keywords: Principal Leadership Styles and Teacher PerformanceAbstrak: Gaya atau cara seorang kepala sekolah dalam kapasitasnya sebagai pemimpin sangat menentukan keberhasilan peningkatan kinerja guru di bawah pimpinannya. Tujuan penelitian ini adalah untuk mendapatkan data tentang (1) gaya kepemimpinan kepala sekolah dalam meningkatkan disiplin kerja, (2) gaya kepemimpinan kepala sekolah dalam meningkatkan motivasi kerja guru, (3) gaya kepemimpinan kepala sekolah dalam meningkatkan tanggung jawab dan  (4) kendala-kendala yang dihadapi kepala sekolah dalam meningkatkan kinerja guru. Melalui pendekatan kualitatif dengan metode deskriptif, teknik pengumpulan data dilakukan melalui wawancara, observasi, dan studi dokumentasi. Penelitian ini menunjukkan bahwa (1) kepala sekolah menerapkan gaya kepemimpinan instruktif (telling) dalam meningkatkan kedisiplinan, (2) kepala sekolah menerapkan gaya kepemimpinan konsultatif (selling) dalam meningkatkan motivasi kerja guru, (3) kepala sekolah menerapkan gaya kepemimpinan delegatif (delegating) dalam meningkatkan tanggung jawab guru, dan (4) kendala-kendala yang dihadapi kepala sekolah yaitu menurunya kedisiplinan guru, kurangnya motivasi kinerja guru, dan rendah rasa tanggung jawab guru dalam pembelajaran. Disarankan agar kepada kepala sekolah dapat menerapkan gaya kepemimpinan yang l